Protein PEGylation for the design of biobetters: from reaction to purification processes - João Henrique Picado Madalena Santos; Karin Mariana Torres-Obreque; Giovanna Pastore Meneguetti; Beatriz Panichi Amaro; Carlota Oliveira Rangel-Yagui (Universidade de São Paulo, 2018)
The covalent attachment of polyethylene glycol (PEG) to therapeutical proteins is an important route to develop biobetters for biomedical, biotech and pharmaceutical industries. PEG conjugation can shield antigenic epitopes of the protein, reduce degradation by proteolytic enzymes, enhance long-term stability and maintain or even improve pharmacokinetic and pharmacodynamics characteristics of the protein drug. Nonetheless, correct information in terms of the PEGylation process from reaction to downstream processing is of paramount importance for the industrial application and processing scale-up. In this review we present and discuss the main steps in protein PEGylation, namely: PEGylation reaction, separation of the products and final characterization of structure and activity of the resulting species. These steps are not trivial tasks, reason why bioprocessing operations based on PEGylated proteins relies on the use of analytical tools according to the specific pharmaceutical conjugate that is being developed. Therefore, the appropriate selection of the technical and analytical methods may ensure success in implementing a feasible industrial process.